Healthcare-associated infections during the coronavirus disease 2019 (COVID-19) pandemic and the modulating effect of centralized surveillance - Graham M. Snyder; Suzanne Wagester; Patricia L. Harris; Abby L. Valek; Jacob C. Hodges; Andrew L. Bilderback; Fazrina Kader; Colleen A. Tanner; Amy P. Metzger; Susan E. DiNucci; Bonnie V. Colaianne; Ashley Chung; et al. (Cambridge University Press, 2023)
We analyzed efficacy of a centralized surveillance infection prevention (CSIP) program in a healthcare system on healthcare-associated infection (HAI) rates amid the coronavirus disease 2019 (COVID-19) pandemic. HAI rates were variable in CSIP and non-CSIP facilities. Central-line-associated bloodstream infection (CLABSI), C. difficile infection (CSI), and surgical-site infection (SSI) rates were negatively correlated with COVID-19 intensity in CSIP facilities.